Developing tools to measure community competence on IMCI program implementation in San Juan, Batangas. - Bibat, Paul Daniel; Barit, Jay-V James G.; Bugarin, Czariane F.; Eleazar, Vittorio V.; Glorioso, Justin Alvin S.; Jimenez, Aliana Christel A.; Lapides, Jomel G.; Medrano, Mark Virgil L.; Mendoza, Gerald Nelson P.; Rodrigo, Carlo Miguel M.; Santiago, Lariela Dianne S. (Manila College of Nursing University of the Philippines Manila, 2011)
This research entitled “Developing Tools to Measure Community Competence on IMCI Program Implementation in San Juan, Batangas” aims to: (1) identify operationalized process indicators for the community competence of San Juan, Batangas on IMCI program implementation; (2) develop an evaluation tool based on the identified process indicators; (3) identify the process indicators for the involvement of the community partners and core group members in fulfilling their three major roles concerning the IMCI program; (4) develop evaluation tools that quantify and qualify the knowledge, skills, and attitudes of community partners and core group members in playing their roles; and (5) determine the validity and reliability of the developed evaluation tools.

To address the aims of the study, the research design of the previous study of Abaca, et. al.
(2006) and Abad, et. al. (2007) was replicated. A multimethod component research design utilizing the participatory action research approach was used to acquire qualitative and quantitative data. Through literature review, focus group discussions with the different sectors of the community, and key informant interviews, themes were analyzed and clustered under the eight dimensions of community competence (Cottrell, 1976; Eng & Parker, 1994), forming the operationalized process indicators on evaluating the community competence of San Juan, Batangas on IMCI program implementation. From these process indicators, two evaluation tools, a questionnaire and an evaluation and observation checklist, were developed.

Through subjecting the evaluation tools to content validity testing with eight experts, the
Average Congruency Percentage (ACP) of the tools were determined: 0.881 for the questionnaire, and 0.90 for the evaluation checklist. Both indices reveal that the evaluation tools have acceptable content validity. As for the interrater reliability of the evaluation and observation checklist, two raters utilized the evaluation tool both at the barangay and municipal level. A Percent Agreement (Po) of 0.91463 was acquired and revealed strong inter-rater reliability. A Cohen’s Kappa (k) value of 0.61883 reveals that there is 0.61 probability that the agreements on the evaluation checklist are reflective of the process indicators observed and not just attributable to chance. Hence, the - interrater reliability indicates a good strength of agreement.

After subjecting the tools to further revisions based on the aforementioned processes, the
revised tools were subjected to further content validity testing and interrater reliability testing. The revised questionnaire yielded an ACP of 0.9286 while the checklist yielded 0.9259 based on the ratings of five experts, signifying increase in strength of content validity. As for the interrater reliability of the checklist, the first pair of raters (BHWs), a Percent Agreement (Po) of 0.899 was acquired and revealed strong inter-rater reliability. A Cohen’s Kappa (k) value of 0.648 reveals that there is 0.648 probability that the agreements on the evaluation checklist are reflective of the process indicators observed and not just attributable to chance alone; hence, a good strength of agreement. As for the second pair of raters (nurses), a Percent Agreement (Po) of 0.91 and a Cohen's Kappa (k) value of 0.67 reveal an increase in the level of reliability of the tool.

These results suggest that the identified indicators of community competence in relation to
IMCI program implementation as reflected in the constructed questionnaire and evaluation
checklist are valid and reliable. In the future conduct of evaluation, these tools could be utilized in evaluating the community competence of San Juan, Batangas in IMCI program implementation.
A collaboration of the People of San Juan, Batangas led by Hon. Mayor Rodolfo H. Manalo, and the Municipal Health Office led by Dr. Nestor Alidio, Jr.
And the University of the Philippines Manila College of Nursing Class 2011.
Accomplishment report (In partial fulfillment of the requirements in N121.2: Intensive Community Experience) -- University of the Philippines Manila, March 2011.
Keywords: Intensive community experience